An Evaluation of management practices and environmental impact of Jong Crocodile Farm, Sarawak - Yong, Corina Siaw Ping. (2001)
Crocodiles population have declined in many parts of the world, and this has been linked to the uncontrolled trade in their skins which took place before the implementation of CITES (Convention Trade in Endangered Species of Wild Fauna and Flora). Since 1975 CITES has stepped in to control trading of crocodile skins, with the aim to conserve the remaining wild crocodile population without jeopardising their comercial values. Crocodile farming is recognised as a solution that could help to increase the crocodile population by rearing of them in captivity as a conservation measure to build up their population numbers and for production of offspring which are raised for commercial production of skin and meat or live animal sales.